Efficacy of methylprednisolone pulse therapy on neuroleptic malignant syndrome in Parkinson's disease. Issue 5 (1st May 2003) - Sato, Y; Asoh, T; Metoki, N; Satoh, K
Abstract : Background: Neuroleptic malignant syndrome (NMS) is a dangerous complication in patients with Parkinson's disease (PD). Aims: To evaluate the efficacy of methylprednisolone pulse therapy compared to placebo in PD patients with NMS. Methods: In a double blind, placebo controlled study, 20 PD patients with NMS received steroid pulse therapy for three days, and 20 PD patients received placebo. Both groups received levodopa, bromocriptine, and dantrolene. Results: NMS in the steroid group healed within 10 days in 17 patients; median value of duration of illness of NMS in this group was 7 days (range 4–20). NMS in the placebo group healed within 10 days in five patients; in the remaining 15, it persisted for 12–27 days after the onset of NMS; median value of duration illness of NMS in this group was 18 days. Hyperthermia, rigidity, and consciousness improved within 10 days in many patients in the steroid group; these signs persisted more than 10 days in many patients in the placebo group. Conclusions: Steroid pulse therapy is useful in NMS for reducing the illness duration and improving symptoms.